2022
DOI: 10.1002/anie.202209210
|View full text |Cite
|
Sign up to set email alerts
|

Inside Cover: Anion‐Guided Stepwise Assembly of High‐Nuclearity Lanthanide Hydroxide Clusters (Angew. Chem. Int. Ed. 33/2022)

Abstract: The rational synthesis … …ofhigh-nuclearity lanthanide clusters remains challenging.Intheir Research Article (e202205385), Min Feng, Zhiping Zheng,and co-workers developed astepwise synthesis of ahigh-nuclearity sodalite cage-like cluster Er 60 ,guided by judiciously selected anions. Thesuccessive introduction of I À ,CO 3 2À ,and NO 3 À led to the isolation of three crucial intermediate clusters,n amely the wheel-like Er 12 ,s hip-like Er 34 ,a nd bowl-like Er 48 . These findings opened the "black box" of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…391,392 In addition, two different research groups revealed two different ways to generate similar Ln 60 clusters. 393,394 By controlling the hydrolysis of Ln(ClO 55 These clusters represent the second largest lanthanide-exclusive cluster to date, while the largest is the {Gd 140 } wheel. 52 These huge Ln oxyhydroxide clusters (Fig.…”
Section: Platonic and Archimedean Solids In Lanthanide-containing Clu...mentioning
confidence: 99%
See 4 more Smart Citations
“…391,392 In addition, two different research groups revealed two different ways to generate similar Ln 60 clusters. 393,394 By controlling the hydrolysis of Ln(ClO 55 These clusters represent the second largest lanthanide-exclusive cluster to date, while the largest is the {Gd 140 } wheel. 52 These huge Ln oxyhydroxide clusters (Fig.…”
Section: Platonic and Archimedean Solids In Lanthanide-containing Clu...mentioning
confidence: 99%
“…[654][655][656] In recent years, with some exploration on the role of various anion templates in directing the multi-step assembly process of high-nuclearity metal clusters, the guiding role of the homo-/hetero-anions in the ''dynamic'' process becomes clearer, which is not limited to the somewhat ''static'' role for directing structure or supporting construction. 387,393,394,501,516,657 Recently, the study by Zheng and Feng provided a rare groundbreaking example, i.e., how to generate a large target-lanthanide hydroxide cluster (Ln 60 cluster with an individual sodalite cage structure, Fig. 42d) through hetero-anion-guided rational stepwise assembly (Fig.…”
Section: Supertetrahedrons In Metal Chalcogenidesmentioning
confidence: 99%
See 3 more Smart Citations